PENERAPAN MODEL PEMBELAJARAN INKUIRI MELALUI PENDEKATAN KONTEKSTUAL (CONTEXTUALTEACHINGLEARNING) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS X MIPA 2 SMA NEGERI 1 TALUN - Purwanto, Sayudi (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2020)
The present study is a classroom action research which is designed in two cycles. Each cycle consists of 4 stages, namely: planning, acting, observing, and reflecting. The data analysis used qualitative-quantitative analysis. The subjects of this study were 39 students of class X MIPA 2 at SMA Negeri 1 Talunwho were taughtthe waste and waste recycling. The results reveal that: 1) the application of the inquiry learning model through a contextual approach (contextual teaching learning) can increase the students’ learning motivation. The motivation aspects, which include attention, connection, self-confidence, and satisfaction, have increased from 1.55% to 4.98%. The highest increase was found in the in confidence aspect; that is,3.73%; 2) the application of the inquiry learning model through a contextual approach (contextual teaching learning) can improve the students’ learning outcomes which involve cognitive, affective, and psychomotor domains.